Education content provider based on particular weaknesses of students: a unsupervised machine learning appro - Rahman, Shabab Intishar; Fariha, Tasnim Akter; Haque, Muhammad Nayeem Mubasshirul; Mohammad, Ammar; Ahmed, Shadman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.